Diverse responses of hypoxia-inducible factor alpha mRNA abundance in fish exposed to low oxygen: the importance of reporting methods - Murphy, Taylor E.; Rees, Bernard B. (Frontiers in Physiology, 2024)
Low dissolved oxygen (hypoxia) poses significant challenges to aquatic ecosystems, affecting the behavior, reproduction, and survival of aquatic organisms. Some fishes respond to hypoxia by changes in gene expression, which may be regulated by the hypoxia inducible factor (HIF) family of transcription factors. HIF abundance and activity depends upon the post-translational modification of the alpha protein subunit, although several studies indicate that HIFA mRNA abundance increases in tissues of fishes exposed to hypoxia. This study reviewed reports of laboratory exposures of adult ray-finned fishes to hypoxia and used generalized linear mixed effects models to examine the influence of HIFA gene, tissue sampled, and exposure conditions in explaining the diversity of responses seen in HIFA mRNA abundance. The frequency of hypoxia-induced increases in HIFA mRNA was poorly explained by gene, tissue, or the severity of the hypoxic exposure. Rather, the frequency of reported increases was strongly related to the extent to which studies adhered to guidelines for documenting quantitative real-time PCR methods: the frequency of hypoxia-induced increases in HIFA mRNA decreased sharply in studies with more thorough description of experimental design. Future research should (a) adhere to stringent reporting of experimental design, (b) address the relative paucity of data on HIF2A and HIF3A, and (c) determine levels of HIF alpha protein subunits. By following these recommendations, it is hoped that a more complete understanding will be gained of the role of the HIF family of transcription factors in the response of fish to hypoxia.